Loss of RUNX3 expression is an independent adverse prognostic factor in diffuse large B-cell lymphoma. Issue 1 (2nd January 2017) - Duncan, Virginia E.; Ping, Zheng; Varambally, Sooryanarayana; Peker, Deniz
Abstract: Runt-related transcription factor-3 (RUNX3) is an apoptotic factor correlated with tumorigenesis and cancer progression. Enhancer of zeste homolog-2 (EZH2), a histone methyltransferase, has been shown to mediate silencing of RUNX3. We investigated RUNX3 and EZH2 expression in diffuse large B-cell lymphoma (DLBCL). A chart review was conducted and tissue-microarray (TMA) was constructed using archived tissue from 83 DLBCL cases. RUNX3 and EZH2 protein expression was correlated with immunophenotypic subtypes and survival. Loss of RUNX3 was observed in 20 cases; EZH2 expression was observed in 59 cases. RUNX3-negative tumors had significantly lower overall and recurrence-free survival (log-rank test, p < 0.0001 for each). No correlation was found between RUNX3 and EZH2 staining ( r = 0.14; p = 0.2). Results suggest a role for the RUNX3 gene in the pathogenesis of DLBCL. Loss of RUNX3 expression strongly correlated with adverse prognosis, independent of subtype. Further studies are warranted to elucidate the biology and prognostic utility of RUNX3 in DLBCL.